A robust noncoherent iterative detection algorithm for serially concatenated CPM - Bing Li; Baoming Bai; Mengyu Huang (2010 6th International Symposium on Turbo Codes & Iterative Information Processing, 2010)
This paper is concerned with the noncoherent soft detection of serially concatenated continuous phase modulation under strong phase noise (PN). We model the noncoherent detection of continuous phase modulation (CPM) as a special case of detection for channel with memory and propose a trellis-based reduced-complexity soft detection algorithm for CPM. The proposed algorithm is developed based on bidirectional Viterbi algorithm. It does not require pilots and signal-to-noise ratio knowledge at the receiver side. By optimizing the parameters, it exhibits considerable robustness and better performance under severe phase noise.